Cell-Based Veterinary Pharmaceuticals – Basic Legal Parameters Set by the Veterinary Pharmaceutical Law and the Genetic Engineering Law of the European Union - Faltus, Timo; Brehm, Walter (Frontiers in Veterinary Science, 2016)
Cell-based therapies have been in use in veterinary medicine for years. However, the legal requirement of manufacturing, placing on the market and use of cell-based veterinary pharmaceuticals are not as well developed as the respective requirements of chemical pharmaceuticals. Cell-based veterinary pharmaceuticals are medicinal products in the sense of the pharmaceutical law of the European Union (EU). For that reason, such medicinal products principally require official approval for their manufacture and an official marketing authorisation for their placement on the market before being used by the veterinarian. The manufacture, placing on the market and use of cell-based veterinary pharmaceuticals without manufacturing approval and marketing authorisation is permitted only in certain exceptional cases determined by EU and individual Member State law. Violations of this requirement may have consequences for the respective veterinarian under criminal law and under the code of professional conduct in the respective Member State. The regular use of cell-based veterinary pharmaceuticals within the scope of a therapeutic emergency as well as the import of such veterinary pharmaceuticals from non-European countries for use in the EU are currently out of the question in the EU because of a lack of legal bases. Here, we review the general legal requirement of manufacturing, placing on the market and use of cell-based veterinary pharmaceuticals within the EU and point out different implementations of EU law within the different Member States.